Perbedaan Filosofis dan Praktis dalam Laporan Keuangan : Perspektif Konvensional vs Syariah - Dede Maman Pathulrahman; Pipit Pipit; Anggia Dhafa Irvani; Tsuwaebatul Aslamiyah; Joni Joni (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
The aim of this study is to examine the philosophical and practical differences between conventional and Islamic financial reports. Laporan keuangan konvensional disusun berdasarkan prinsip-prinsip ekonomi kapitalis, dengan orientasi pada laba dan kepentingan pemegang saham. Meanwhile, Islamic financial reports are based on Islamic principles that emphasise justice, transparency, and social responsibility, as well as holding financial activities accountable not only to humans, but also to Allah SWT. The research method used was qualitative descriptive-comparative through a literature study of accounting standards and related journals. The results of the study show differences in reporting objectives, report structure, basic principles, transaction measurement methods, and stakeholder orientation. Laporan syariah mencakup unsur-unsur tambahan, seperti laporan zakat, qardh, dan tanggung jawab sosial, yang tidak ditemukan dalam sistem konvensional. Memahami perbedaan ini sangatlah penting untuk mempromosikan praktik pelaporan keuangan yang tidak hanya berorientasi pada keuntungan, tetapi juga menjunjung tinggi nilai-nilai etika dan keberlanjutan.